2005
DOI: 10.1152/ajpendo.00366.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of 17β-estradiol and raloxifene on VSMC phenotype and expression of osteoblast-associated proteins

Abstract: Rzewuska-Lech, Ewa, Muthuvel Jayachandran, Lorraine A. Fitzpatrick, and Virginia M. Miller. Differential effects of 17␤-estradiol and raloxifene on VSMC phenotype and expression of osteoblast-associated proteins. Am J Physiol Endocrinol Metab 289: E105-E112, 2005. First published February 15, 2005 doi:10.1152/ajpendo.00366.2004.-Several studies demonstrate an association between osteoporosis and arterial calcific disease, both of which being common in elderly women. Estradiol and raloxifene, a selective estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 66 publications
5
25
0
Order By: Relevance
“…The in vitro studies have shown that estradiol or raloxifene maintain VSMCs' OPG production when cultured under elevated levels of calcium phosphates [22]. We have confirmed that under calcification-promoting conditions, endothelial cells change the sRANKL and OPG release.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The in vitro studies have shown that estradiol or raloxifene maintain VSMCs' OPG production when cultured under elevated levels of calcium phosphates [22]. We have confirmed that under calcification-promoting conditions, endothelial cells change the sRANKL and OPG release.…”
Section: Discussionsupporting
confidence: 73%
“…That day, when we administered substances described above was called day 0. Concentrations of raloxifene and estradiol were established on the basis of literature for efficacy at physiological levels [22]. Medium was changed at day 1, 2 and 4.…”
Section: Cell Culture -Human Umbilical Vein Endothelial Cells (Huvec)mentioning
confidence: 99%
“…In clinical studies, a low serum estradiol level in women was correlated with increased arterial calcification (37), and estrogen replacement could reduce coronary calcification (38,39). However, in experimental studies, estradiol treatment showed variable effects on vascular calcification with either inhibition (40,41) or stimulation of calcification (42). Further studies are needed to elucidate the actions of estrogens in vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…These data support a cardiovascular protective effect of CEE in women for whom estrogenic treatments would not be prescribed under the current practice guidelines. Mechanisms by which estrogen reduces calcification are multifactorial but most likely include modulation of cell differentiation Abedin et al, 2004;Rzewuska-Lech et al, 2005), genetic variation related to bone matrix proteins and osteoblast/clast activation (Doherty et al, 2003), and perhaps susceptibility to infection by calcifying nanoparticles (Miller et al, 2004b). Much remains to be learned about the contribution of specific estrogen receptors in arterial calcific processes.…”
Section: B Atherosclerosismentioning
confidence: 99%